Factors Associated with Anemia Among Adolescence Girls at SMAN 1 Telukjambe Kabupaten Karawang in 2015 - Fitrianti, L; Yunis Miko, T (KnE Life Sciences, 2019)
This study aimed to determine factors related to anemia among adolescent girls at the SMAN 1 Telukjambe Kabupaten Karawang in December 2015. A cross-sectional study is conducted to determine the hemoglobin, food intake, physical examination. A total of 92 girls selected in random. An interviewer-administered questionnaire was used to collect information on their characteristics and food consumption, knowledge of anemia, infections, and other, other relevant factors. The prevalence was a measured percentage and the association between anemia and identified factors explored through bivariate analyses. The results showed that the prevalence of anemia was 44.6%; consumption of protein, fruit, and knowledge significant associated with anemia but not other factors. Keywords: Anemia, Adolescence girls.